Peran Perpustakaan Digital: Meningkatkan Minat Baca Mahasiswa - Nazala, Cetryna Fais (Maliki Interdisciplinary Journal, 2026)
The development of information technology has brought major changes to the world of education, including library services. Digital libraries have emerged as a modern solution that makes it easier for students to access various sources of information quickly, flexibly, and without space and time limitations. This study aims to examine the role of digital libraries in increasing students’ interest in reading in the digital age. The method used is a literature study by reviewing various relevant journals and scientific sources. The results show that digital libraries have a positive impact on increasing students’ interest in reading through easy access to collections, diversity of reading materials, and technological support such as e-books and quick search features. In addition, digital libraries also play a role in improving students’ information literacy and critical thinking skills. However, the use of digital libraries still faces several challenges, such as limited digital literacy, concentration distractions when reading through electronic devices, and technical network constraints. Therefore, efforts to strengthen digital literacy and optimize digital library services are needed so that they can be utilized optimally in improving the reading culture of students.